Maggi Noodles: Magic of the 2-Minute Campaign - Kamboj, Rajni (Indian Journal of Marketing, 2012)
The Indian FMCG sector is the fourth largest sector in the economy, with a total market size in excess of US 13.1 billion. Availability of key raw materials, cheaper labour costs and presence across the entire value chain gives India a competitive advantage. The FMCG market is set to treble from US 11.6 billion in 2003 to US 33.4 billion in 2015. According to a study by McKinsey & Company, the Indian food market is poised to grow US 310 billion by 2015 and US 344 billion in 2025 - at an approximate compounded annual growth rate of 4.10%. India’s food-processing industry is one of the largest industries in the country - it is ranked fifth in terms of production, consumption, export and expected growth. India is one of the world’s major food producers, but accounts for only 1.7% (US 7.5 billion) of the world trade in this sector - this share is slated to increase to 3% (US 20 billion) by 2015. According to the Ministry of Food Processing, this industry contributed 9% to India’s GDP and had a share of 6% in the total industrial production. The industry employs 1.6 million workers directly. Noodles market in India is not smaller. It’s around a 1500 crore business in the country. The case examines a detailed account of NestlÃ©’s promotion and advertising strategies for creating a noodles market from scratch. This case looks at the various phases in the product life cycle of Maggi noodles in India. It talks about the various measures taken by NIL to keep the Maggi brand fresh in the minds of the Indian consumers and reposition Maggi as a ’Health product’. It ends with a discussion whether NIL would be successful in sustaining this new image for Maggi in the future or not.